Teaching Competencies of Students Practice Teaching at Elementary Schools and Kindergartens - Nur Fatimah (Intelektual Pustaka Media Utama, 2012)
The objective of this study is to describe the teaching competencies of English Education students practising at elementary schools and kindergartens based on the teacher supervisors’ view. The teaching competencies include the students’ competence on writing the lesson plan and their competence on practice teaching. To reach the objectives of the study, the researcher collected the data by distributing a questionnaire to the supervisors at schools. There were 41 schools consisting of TK ABA, SD Muhammadiyah, SD Negeri located in Yogyakarta (24), Sleman (1) and Bantul (16). The questionnaire used was based on the official assessment form published by Indonesian government for teacher’s certification. It contains some indicators of teaching competence, it uses Likert scales ranging from 1 to 5. The criteria are as follows: 1 = very poor, 2 = poor, 3 = rather poor, 4 = good, and 5 = excellent. The data were taken from proportionally random sampling of the supervisors. From the total number of 103 teacher supervisors, the researcher distributed 61 questionnaires. The supervisors represented the ones from different educational backgrounds. The findings show the following results. The competence of English Education students in composing the lesson plan, according to the teacher supervisors, is classified good (actual mean = 3.858, SD = 0.685, ideal mean = 3, ideal SD = 0.750). Further, their competence on practice teaching is also good (actual mean = 3.867, SD = 0.688, ideal mean = 3, ideal SD = 0.966). The two aspects of composing the lesson plan to improve are teaching material organization and the completeness of assessment instrument. The other two aspects to improve in teaching practice are contextual teaching and learning and class management.